2021
DOI: 10.1002/smll.202007102
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Propelled Nano and Micromotors in the Body: Quo Vadis?

Abstract: The active delivery of drugs to disease sites in response to specific biomarkers is a holy grail in theranostics. If successful, it would greatly diminish the therapeutic dosage and reduce collateral cytotoxicity. In this context, the development of nano and micromotors that are able to harvest local energy to move directionally is an important breakthrough. However, serious hurdles remain before such active systems can be employed in vivo in therapeutic applications. Such motors and their energy sources must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 87 publications
(107 reference statements)
0
24
0
Order By: Relevance
“…Recent studies have shown that ensembles of single enzyme molecules, as well as enzyme-attached microparticles, also chemotax in response to a gradient of the substrate. This phenomenon has been exploited to direct the motion of enzymes and enzyme-attached particles to specific locations in space, e.g., for drug delivery applications. Despite the importance of the phenomenon and the myriad of applications that stem from it, the mechanistic basis of chemotaxis in synthetic systems remains poorly understood. For example, it has been suggested that chemotaxis requires that the motile particles possess an active coupling of their orientation to the chemical gradient .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ensembles of single enzyme molecules, as well as enzyme-attached microparticles, also chemotax in response to a gradient of the substrate. This phenomenon has been exploited to direct the motion of enzymes and enzyme-attached particles to specific locations in space, e.g., for drug delivery applications. Despite the importance of the phenomenon and the myriad of applications that stem from it, the mechanistic basis of chemotaxis in synthetic systems remains poorly understood. For example, it has been suggested that chemotaxis requires that the motile particles possess an active coupling of their orientation to the chemical gradient .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has tended to exploit the motion of synthetic swimmers near boundaries, where non-slip conditions minimize flow velocity, drag force is reduced, and upstream manipulation is easier. Catalytic approaches have been widely investigated (17)(18)(19)(20)(21)(22), and Katuri et al demonstrated a controlled crossstream motion of janus particles, which could mimic the motion of natural microswimmers and be exploited to reach vessel boundaries (23). Importantly, some approaches have already managed to manipulate microswimmers upstream when they are close to a wall.…”
Section: Introductionmentioning
confidence: 99%
“…1−7 In comparison to conventional nanocarriers, the nano/micromotors offer several advantages for cell internalization, including enhanced adhesion, better penetration, and a shorter and controllable transporting time based on the propelling mechanism. 8−12 Early studies in the synthesis and application of nano/micromotors focused only on designs based on micromotor motions powered by magnetic, 13 ultrasound, 14−16 and chemical propulsion mechanisms 17,18 and their combinations. 19,20 Chemical propulsion is fast motion, but fuels can have a toxic effect, which limits biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial micro- and nanomotors have fascinating capability to move autonomously or under different external energy sources. These molecular machines play an important role in the development of medical applications including active drug delivery, fast detection of tumor markers, and payload transport into cells. In comparison to conventional nanocarriers, the nano/micromotors offer several advantages for cell internalization, including enhanced adhesion, better penetration, and a shorter and controllable transporting time based on the propelling mechanism. Early studies in the synthesis and application of nano/micromotors focused only on designs based on micromotor motions powered by magnetic, ultrasound, and chemical propulsion mechanisms , and their combinations. , Chemical propulsion is fast motion, but fuels can have a toxic effect, which limits biological applications. Unlike chemical propulsion, acoustic propulsion especially offers a unique opportunity to use such microscale devices in biological applications because of its non-toxic fuel requirement, tunability, and prolonged operation time .…”
Section: Introductionmentioning
confidence: 99%